Baroclinic Transport Time Series of the Antarctic Circumpolar Current Measured in Drake Passage - Chidichimo, María Paz; Donohue, Kathleen A.; Watts, D. Randolph; Tracey, Karen L. (Journal of Physical Oceanography)
The first multiyear continuous time series of Antarctic Circumpolar Current (ACC) baroclinic transport through Drake Passage measured by moored observations is presented. From 2007 to 2011, 19 current- and pressure-recording inverted echo sounders and 3 current-meter moorings were deployed in Drake Passage to monitor the transport during the cDrake experiment. Full-depth ACC baroclinic transport relative to the bottom has a mean strength of 127.7 ± 1.0 Sverdrups (Sv; 1 Sv = 106 m3 s-1) with a standard deviation of 8.1 Sv. Mean annual baroclinic transport is remarkably steady. About 65% of the baroclinic transport variance is associated with time periods shorter than 60 days with peaks at 20 and 55 days. Nearly 28% of apparent energy in the spectrum computed from transport subsampled at the 10-day repeat cycle of the Jason altimeter results from aliasing of high-frequency signals. Approximately 80% of the total baroclinic transport is carried by the Subantarctic Front and the Polar Front. Partitioning the baroclinic transport among neutral density γn layers gives 39.2 Sv for Subantarctic Surface Water and Antarctic Intermediate Water (γn < 27.5 kg m-3), 57.5 Sv for Upper Circumpolar Deep Water (27.5 < γn < 28.0 kg m-3), 27.7 Sv for Lower Circumpolar Deep Water (28.0 < γn < 28.2 kg m-3), and 3.3 Sv for Antarctic Bottom Water (γn > 28.2 kg m-3). The transport standard deviation in these layers decreases with depth (4.0, 3.1, 2.1, and 1.1 Sv, respectively). The transport associated with each of these water masses is statistically steady. The ACC baroclinic transport exhibits considerable variability and is a major contributor to total ACC transport variability. Fil: Chidichimo, María Paz. University of Rhode Island. Graduate School of Oceanography; Estados Unidos. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Defensa. Armada Argentina. Servicio de Hidrografía Naval. Departamento Oceanografía; Argentina Fil: Donohue, Kathleen A. University of Rhode Island. ...